2013
DOI: 10.1080/10288457.2013.848540
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Self-directed Professional Development: Science and Mathematics teachers’ adoption of ICT as a professional development strategy

Abstract: This paper is part of a larger study that was carried out to investigate the use of information communication technology (ICT) in the self-directed professional development (SDPD) of mathematics and science teachers in Zimbabwe. The educational context provides an example of how teachers compensated for lack of structured government initiatives to support teachers' professional development. This paper focuses on the ways in which these teachers were using ICT resources to further their professional development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…This finding confirms the positive attitudes of English language teachers towards the use of the Internet for professional development, an issue that has been pointed out by previous studies (e.g., Schrum, 1995;Herrington & Herrington, 2006;Charalambous & Ioannou, 2008;Demir, 2010;Mushayikwa, 2013;Rolando, Salvador, & Luz, 2013). This finding here encourages policy-makers in Arab countries to consider the Internet as a pivotal aspect of language educators lives.…”
Section: Teachers' Use Of the Internetsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding confirms the positive attitudes of English language teachers towards the use of the Internet for professional development, an issue that has been pointed out by previous studies (e.g., Schrum, 1995;Herrington & Herrington, 2006;Charalambous & Ioannou, 2008;Demir, 2010;Mushayikwa, 2013;Rolando, Salvador, & Luz, 2013). This finding here encourages policy-makers in Arab countries to consider the Internet as a pivotal aspect of language educators lives.…”
Section: Teachers' Use Of the Internetsupporting
confidence: 78%
“…In Brazil, Rolando, Salvador, and Luz (2013) found that biology teachers made limited use of the Internet and ICTs for educational purposes, with a rare use of the Internet for didactics purposes. In Zimbabwe, Mushayikwa (2013) recently investigated the use of ICTs for self-directed professional development by mathematics and science teachers and pointed out that the majority of Zimbabwean teachers had difficulties in accessing the Internet which had its impact on their use of ICTs for professional development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-Initiated Professional Development (SI-PD) is a professional development that arises from teacher's own initiative which to develop their intellect, experience as well as attitude and internally motivated (Mushayikwa, 2013). It is a new approach of professional development in Malaysia and most of the teachers still unfamiliar with it, thus they still need supports because sometimes teachers do not always recognize what they do not know (Riddle, 2018;Louws et al, 2017;Noorriati et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many of these techniques, however, rely on self-directed motivated teachers to enhance their own practice. The dangers of this self-directed PD are that teachers either do not have access to the proper equipment such as computers or simply use the PD time to access new resources without enhancing their own practice (Mushayikwa, 2013)…”
Section: Literature Reviewmentioning
confidence: 99%